A resilience lens on the mental health of adolescents in selected low-middle-income sub-Saharan African countries - Ebersohn, L. (Liesel) (University of Pretoria, 2023)
Thesis (PhD (Learning Support, Guidance and Counselling))--University of Pretoria, 2022.